Trauma-induced long-term alterations of human T cells and monocytes: results of an explorative, cross-sectional study - Ruhrmann, Sophie; Schneck, Emmanuel; Markmann, Melanie; Zink, Jan; Zajonz, Thomas Simon; Arens, Christoph; Uhle, Florian; Sander, Michael; Koch, Christian (Shock, 2020)
Background: Major trauma leads to complex immune reactions, known to result in a transient immunodeficiency. The long-term consequences of severe trauma on immune function and regulation as well as its clinical impact remain unclear. Methods: Six months (ranging from −12 to +5 days) after a major trauma event, 12 former trauma patients (Injury Severity Score ≥ 16) and 12 healthy volunteers were enrolled. The current clinical status and infection history since discharge were assessed by a standardized questionnaire. Immune cell subsets (cluster of differentiation (CD)4+, CD8+, CD14+), cell surface receptor expression (programmed cell death protein 1 (PD-1), B- and T-lymphocyte attenuator (BTLA), cytotoxic T-lymphocyte-associated protein 4, toll-like receptor (TLR)-2, -4, and -5, Dectin-1, programmed death ligand 1 (PD-1L)), and human leucocyte antigen D-related receptor (HLA-DR)-expression were quantified by flow cytometry. Cytokine secretion (IL-2, -4, -6, -10, and 17A, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ) was assessed after stimulation of whole blood with LPS-, α-CD3/28, or zymosan. Results: Analysis of surface receptors on T cells revealed a significant elevation of PD-1 expression on CD4+ T cells, whereas BTLA expression on CD4+ and CD8+ T cells was significantly suppressed in the trauma cohort. Monocytes showed a significantly reduced expression of TLR-2 and -4 as well as a reduced proportion of TLR-4 monocytes. HLA-DR receptor density revealed no significant changes between both cohorts. LPS-induced IL-6 and TNF-α secretion showed non-significant trends toward reduced values. No differences regarding clinical apparent infections could be detected. Conclusions: Six months following major trauma, changes of cell surface receptors on CD4+ and CD8+ T cells as well as on CD14+ monocytes were present, hinting toward an immunosuppressive phenotype. Following major trauma, although IL-6 and TNF-α release after stimulation were reduced, they did not reach statistical significance. Overall, further studies are necessary to evaluate the clinical implications of these findings.